2021
DOI: 10.1128/msphere.00218-21
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and Erratic Movement Patterns of Syringe-Injected versus Mosquito-Inoculated Malaria Sporozoites Underlie Decreased Infectivity

Abstract: Malaria vaccine candidates based on live, attenuated sporozoites have led to high levels of protection. However, their efficacy critically depends on the sporozoites’ ability to reach and infect the host liver. Administration via mosquito inoculation is by far the most potent method for inducing immunity but highly impractical. Here, we observed that intradermal syringe-injected Plasmodium berghei sporozoites (syrSPZ) were 3-fold less efficient in migrating to and infecting mouse liver than mosquito-inoculated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Registered coordinates of the DROP‐IN Probe tip allowed us to reconstruct its movement trajectory over time. In line with our previous works, [ 9,14b,16a,26 ] the digitized track allowed us to use custom algorithms (MATLAB, the MathWorks Inc., MA, USA) to extract kinematic metrics such as straightness index, angular dispersion, and adjusted speed. To eliminate the effect of camera location and zooming, the adjusted speed was considered as percentage of position change in each time point.…”
Section: Methodsmentioning
confidence: 94%
“…Registered coordinates of the DROP‐IN Probe tip allowed us to reconstruct its movement trajectory over time. In line with our previous works, [ 9,14b,16a,26 ] the digitized track allowed us to use custom algorithms (MATLAB, the MathWorks Inc., MA, USA) to extract kinematic metrics such as straightness index, angular dispersion, and adjusted speed. To eliminate the effect of camera location and zooming, the adjusted speed was considered as percentage of position change in each time point.…”
Section: Methodsmentioning
confidence: 94%
“…We expect that these ultra-low volumes will still be necessary when scaling up ID-RAS to larger animal models or humans. Inoculation in ultra-low volumes improves spz motility in the skin and allows spz to efficiently invade blood vessels and lymph to home to the liver and dLN, respectively 34 . In our report, 2.5 µL was selected as the smallest volume that could be reliably prepared in the research laboratory for pre-clinical mouse injections.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that the reason for ID spz administration failure may be due to the more tolerogenic environment of the skin, which could ultimately lead to more regulatory immune responses in the liver 25 , 30 . However, most of these studies used standard ID injection volumes (10–50 µL), which do not mimic the ultra-low volumes delivered by probing mosquitoes 31 , 32 , nor facilitate efficient exit of spz from the skin, since spz must move by contact-dependent motility 33 , 34 . Based on the available data, and recognition of this unique biology and motility requirements of spz, we hypothesized that two key aspects of RAS administration are critical for effective ID vaccination: 1) the injection volume must be compatible with the contact-dependent motility of the spz, and 2) the tolerogenic skin immune environment must be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also suggested that the reason for ID spz administration failure may be due to the spz inducing a more tolerogenic skin environment, which could ultimately lead to more regulatory immune responses in the liver [ 25 , 30 ]. However, most of these studies used standard ID injection volumes (10–50 μL), which do not mimic the ultra-low volumes delivered by probing mosquitoes [ 31 , 32 ], nor facilitate efficient exit of spz from the skin, since spz must move by contact-dependent motility [ 33 , 34 ]. Based on the available data, and recognition of this unique biology and motility requirements of spz, we hypothesized that two key aspects of RAS administration are critical for effective ID vaccination: 1) the injection volume must be compatible with the contact-dependent motility of the spz, and 2) the tolerogenic skin immune environment must be overcome.…”
Section: Introductionmentioning
confidence: 99%